Efficacy of galcanezumab in patients with chronic migraine and a history of preventive treatment failure - Ruff, Dustin D; Ford, Janet H; Tockhorn-Heidenreich, Antje; Sexson, Matthew; Govindan, Sriram; Pearlman, Eric M; Wang, Shuu-Jiun; Khan, Arif; Aurora, Sheena K (Cephalalgia, 2019)
Background Efficacy of galcanezumab in chronic migraine has been demonstrated in a pivotal Phase 3 study. Here, we assess efficacy in patients who have failed ≥2 and ≥1 prior migraine preventives for efficacy and/or safety reasons, and in those who never failed. Study design/methods REGAIN (NCT02614261) was a Phase 3, randomized, double-blind, placebo-controlled study in patients with chronic migraine. Patients were randomized 2:1:1 to receive placebo, galcanezumab 120 mg/240 mg once monthly during a double-blind treatment period lasting three months. Subgroup analyses were conducted among patients who failed ≥2 and ≥1 prior preventives and who never failed previously. Outcomes assessed were change from baseline in number of monthly migraine headache days, proportion of patients with ≥50% and ≥75% response (reduction in monthly migraine headache days), change in number of monthly migraine headache days with acute medication use and change in patient functioning per Migraine-Specific Quality of Life Questionnaire Role Function Restrictive (MSQ RF-R) domain score. Results Treatment with galcanezumab versus placebo resulted in significant improvements (p < 0.01) in overall reduction (Months 1–3) from baseline in the number of monthly migraine headache days in patients with prior failures (LS mean change [SE]: ≥2 prior failures: galcanezumab 120 mg: −5.35 (0.71); galcanezumab 240 mg: −2.77 (0.66); placebo: −1.01 (0.54); ≥1 prior failures: galcanezumab 120 mg: −5.53 (0.60), galcanezumab 240 mg: −3.53 (0.59); placebo: −2.02 (0.49). Similarly, significant results were seen with galcanezumab versus placebo for ≥50% and ≥75% response rates, reductions in acute medication use and improvements in MSQ RF-R domain score. In the subgroup with no prior preventive failures, results were statistically significant for the 240 mg galcanezumab group versus placebo on all outcome measures, and for the 120 mg group on the reduction in migraine headache days with acute medication use. There was also a higher placebo response observed in the patients with no prior preventive failures. Conclusion Galcanezumab is consistently efficacious versus placebo in reducing monthly migraine headache days and several other key outcomes in patients with chronic migraine who have failed ≥2 or ≥1 preventives previously. In the subgroup with no prior failures, greater numerical differences were seen with galcanezumab, but statistical separation from placebo varied by dose and outcome. Clinicaltrials.gov identifier number NCT02614261.